FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY PEMERINTAH PROVINSI DI PULAU SUMATERA - Azhara, Kamilah; Rachma Sari, Kartika; Indriasari, Desi (Jurnal Riset Terapan Akuntansi, 2024)
The purpose of this study was to determine the effect of audit findings, the level of regional financial dependence, and the size of the local government on the audit delay of the provincial government on the island of Sumatra. The population in this study were all provinces on the island of Sumatra. The data collection technique uses a saturated sample where all members of the population are sampled. This study uses multiple regression analysis with SPSS version 29. The results revealed that Audit Findings and the Level of Regional Financial Dependence had a negative effect on Audit Delay. Meanwhile, Local Government Size has no effect on Audit Delay. The Adjusted R2 value of 0.137 means that Audit Findings, Regional Financial Dependency Level, and Local Government Size have an effect of 13.7% on Audit Delay with other factors not covered in this study amounting to the remaining 86.3%. The results of the study can provide implications that the Provincial government on the island of Sumatra must be more timely in preparing financial reports so that Audit Delay can be minimized. Keywords: Audit Delay, Audit Findings, Level of Local Financial Dependency, and Local Government